Perancangan Alat Bantu Komunikasi Untuk Pasien Pasca Stroke Dengan Sensor Suhu - Muhammad Hamdy Maadjid; Azriyenni Azriyenni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Stroke is a neurological emergency, the morbidity rate is increasing from year to year. According to the World Health Organization, 15 million people suffer a stroke worldwide every year. Patients with post-stroke disabilities will have difficulty in carrying out daily activities, especially in communicating with other people. Therefore, a post-stroke patient communication tool was made with a temperature sensor that aims to make it easier for post-stroke patients to be able to communicate for a better quality of life. This communication aid is in the form of gloves which are paired with 5 Flex Sensors as movement signal readers which will then be processed by Arduino Nano, this tool is also equipped with a DS18B20 temperature sensor and a pulse sensor that will monitor the physical condition of post-stroke patients in real time, output data in the form of characters and sounds, for characters will be displayed by the LCD and for sound will be played using a speaker where voice data will be called up by the mini DFPlayer module. Keywords: post stroke aids, Arduino nano, Flex Sensor, DS18B20 Temperature Sensor, Pulse Sensor Sensor